Impact of Tick Infestations on Haematological Profile and Health in Labrador Dogs - Chaitanya Gollu; R.Venkata Manoj; D.Kavin; J.Nikhil Kumar Tej; S.K.I.Vasantha; B.V.S.Bhavya Charitha; Deepthi Chandaka (The Indian Veterinary Journal, 2026)
The present study aimed to evaluate the effect of tick infestations on hematological profile in male Labrador dogs. A total of 20 adult male Labrador dogs were randomly selected for the study and they were divided into two groups: GI: control (healthy animals, n=10) and GII: infected (tick-infested, n=10). Whole blood was collected by venipuncture into EDTA vacutainers and used for the estimation of haematological parameters. Analysis of the data revealed that total erythrocyte count, hemoglobin and packed cell volume were significantly (P